Coral mortality and fish abundance in the Marine Nature Reserve of the Eastern Coast of Weh Island, Sabang, Aceh - Nadia Aldyza; Afkar Afkar; Mauizah Hasanah; Cut Roswita (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
Coral reefs play an important role in marine ecosystems as habitats for various species of fish and other marine organisms, as well as protecting the coast from erosion and storms. However, climate change, pollution, human activities, and bleaching have resulted in declining coral conditions. The purpose of this study was to analyze the level of coral mortality and its effect on the abundance of coral fish. The study was conducted in the coastal nature reserve area of East Weh Island. Data collection was carried out at two depths using the Belt Transect method and the Underwater Visual Census technique. The results showed that the level of coral mortality in the coastal nature reserve area of East Weh Island reached 0.82 ± 0.05% at Reuteuk station. These results show that coral conditions in the protected area have a very high mortality rate. However, the high coral mortality in the area did not affect the abundance of coral fish (p-value > 0.05). This value indicates that coral fish can be found abundantly in damaged coral areas. The average results of coral mortality and abundance of coral fish at depths of 3 meters and 7 meters showed no significant difference. These results illustrate that at shallow or deep depths, coral and coral fish mortality can be found at high/abundant values.